Inter-root soil bacterial community composition and its driving factors in Ulmus pumila L. of different ages - Hu, Bo; Ma, Yunxia; Li, Gangtie (Frontiers in Environmental Science, 2025)
Ulmus pumila L: is the primary tree species in the Hunshandake Sandy Land and plays a crucial role in controlling wind and sand movement and stabilizing the soil. Currently, Ulmus pumila L. is aging severely, and the inter-root bacterial community structure directly affects its resistance and nutrient uptake. Therefore, it is crucial to investigate the composition of the inter-root soil bacterial community and its driving factors during elm growth. In this study, high-throughput sequencing technology was utilized to determine the bacterial community composition and reveal the relationship between the inter-root bacterial community composition of U. pumila L. of different ages and microenvironmental factors based on basic soil properties and enzyme activities. The results showed that alkaline phosphatase and soil invertase levels increased with the increasing stand age. Compared with young forests (YF), soil total nitrogen, total phosphorus, and organic carbon in mature forests (MF) increased by 32.20%, 33.73%, and 17.65%, respectively. The contents of soil available nitrogen (AN) and available phosphorus showed the same trend in different forest ages. The variation trends of the total number of species and specific species of inter-root soil bacteria in U. pumila L. were consistent, and both showed a downward trend. Actinobacteria were significantly more abundant in young forests than in the others (P < 0.05). It showed a decreasing trend, and mature forests decreased by 29.23% compared to YF, while the abundance of Firmicutes increased. The results of the RDA analysis suggested that available nitrogen explained the most changes in soil bacterial community structure. AK and AN were strongly negatively correlated with Firmicutes but positively correlated with all other bacteria. This study provides useful information for the conservation and utilization of sparse elm forests and also helps provide a vital theoretical basis for understanding the ecological environment construction in the Hunshandake Sandy Land.